Analisis Hubungan Return Saham, Trading Volume, dan BI Rate pada Saham Sektor Pertambangan - Silvia Hendrayanti (Jurnal Ilmiah Aset, 2017)
The capital market is one of investment alternative that able to yield optimal advantage for investor. This is very important to be made in consideration in compiling strategy and decision making of investment in capital market. The objectives of this research to analyze Stock Return, Trading Volume, and BI Rate in Stock of Mining Sector This research using time series data from BEI and Indonesian Bank. Population in this research is the mining sector in Indonesia during the observation period January 2007 until December 2015. Totality of the sample which has been used in this study was 108 samples (period January 2007 until December 2015 which consists of 52 issuers.The research method is by using descriptive analysis, stationary test, VAR analysis, Granger causality test, Impulse response anlysis, and variance decomposition analysis. Hypothesis test (t-statistic test, F-statistics test, and coefficient of determination test (R2)). The result of this research shows that Stock return(-1)& Stock return(-2) variable has a positive and significant to Trading volume, Trading volume(-1)& Trading volume(-2) variable has a negative and not significant to stock return, BI Rate variable has a negative and significant to stock return, BI Rate variable has a negative and significant to Trading volume.